A Post-Colonial Analysis of Bilateral Tourism Flows: the Case of Korea and Japan - Kim, Seongseop; Prideaux, Bruce (The international journal of tourism research, 2012)
ABSTRACT Rapid decolonization began after World War II (1939–1945) and did not conclude until the breakup of the former USSR in 1989. Many studies have labelled tourism as the peace industry. However, there have been limited efforts to analyze post‐colonial tourism exchanges between colonizers and the colonized. This study explored the development of post‐colonial tourism exchanges between Japan and South Korea in the period 1946–2010. The high level of residual mistrust and diplomatic disputes that affected bilateral flows in the years after Korea's independence from Japan have now been replaced by a very high level of bilateral flows between the two nations, indicating that many of the issues of the past are no longer seen as relevant by contemporary Korean and Japanese tourists. The paper suggests a framework for analysing post‐colonial flows. Copyright © 2011 John Wiley & Sons, Ltd.